AREAS WITH SPECIAL STATUS IN EUROPEAN UNION COUNTRIES - Maria-Cristiana IEREMIE (Challenges of the Knowledge Society)
In a unitary state, as a rule, the administrative-territorial organization is unitary to the same extent, at least from the perspective of the legal regime. However, every rule has an exception, which is why we can observe the same situation with regard to certain areas whose situation is expressly provided by the fundamental law of each state. It is also the case of several countries that we will study in the content of this article where we will exemplify the legal regime of areas with special status.